PENERAPAN REKAM MEDIS ELEKTRONIK DALAM PELAYANAN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH (RSUD) LABUANG BAJI PROVINSI SULAWESI SELATAN - Moh. Amrullah; Ahmad Sulaiman; Hasnawati S (Yayasan Nuraini Ibrahim Mandiri, 2025)
Background: Advances in information technology now play an important role in various sectors of life, one of which is the health sector. One form of information technology implementation that is currently a global trend in health services is Electronic Medical Records (EMR). This study aims to assess the extent of the implementation of electronic medical records in inpatient services at Labuang Baji Regional General Hospital (RSUD) in South Sulawesi Province. Research Method: This type of research uses a mixed-method approach, which is a combination of quantitative and qualitative methods to obtain a more comprehensive understanding of the implementation of Electronic Medical Records (EMR) in hospitals. The quantitative approach is used through descriptive-analytic research design with a cross-sectional approach, as well as the application of the DOQ-IT (Digital Organizational Quality - Implementation Tool) method.Sample: The sample size was 71 employees involved in the use of electronic medical records at Labuang Baji Regional General Hospital (RSUD) in South Sulawesi Province. Research Results: The quantitative results show that the implementation of EMR in the human resources component scored 3.75, which falls into the